(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Mandryka T., Mikhailenko N. The role and place of ICT in the teaching of psycho-pedagogical disciplines. It is rotined in the article, what information technologies and on what stages of teaching use in a teaching-edukated process in Higher Educational Establishments І-ІІ levels of accreditation. In fact for today without the use of ICT it is impossible to provide equal access to high-quality education for all students.